Trends in International Co-authorship of Russian Scientists During 2019–2023 According to OpenAlex Data - Yu. V. Mokhnacheva (Библиосфера)
Collaboration in science is essential and often considered a necessary condition for improving the quality of research. Identifying the changing trends in international scientific cooperation is a crucial task of scientometrics. The purpose of this study is to analyze the trends in Russia’s collaboration with major partner countries. The objectives of the research are: 1. To compare the dynamics of joint publication activity between Russia with two groups of countries – the “BRICS plus” countries and the several Western countries and Japan. 2. To determine the “weight” of publication arrays based on their citation rates compared to the global average ones. The object of the analysis is the array of Russian publications written in collaboration with scientists from the “BRICS plus” countries and several Western countries and Japan. The data source is the OpenAlex open-access resource. The study found that co-authorship between Russian scientists and representatives of the several Western countries and Japan has been actively decreasing in all fields of knowledge, although it is still at a high level in quantitative terms. The citation rates of documents published in collaboration with these countries have been higher than the global average in 14 out of 26 scientific fields. However, joint publication activity with the “BRICS plus” countries is still low. Nevertheless, the average citation rates of publications with these countries in 12 fields exceed the global average, indicating a tangible benefit from scientific cooperation. Trends towards increased joint publication activity have been observed in all fields, to varying degrees, with representatives of the “BRICS plus” countries. The study of bilateral publication relationships has shown that collaboration with Russian colleagues contributes the most to the publication output of Belarus and Kazakhstan.